Analisis Faktor Penyebab Rendahnya Hasil Belajar Mata Pelajaran PAI-BP Kelas Tinggi di SD Negeri 166/III Cut Mutia - Rimadhanty, Ayuning; sulaiman, Sulaiman (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study has the aim of specifically describing what factors influence the low learning outcomes of high-grade PAI-BP at SD Negeri 166/III Cut Mutia Kerinci Jambi. This research is a quantitative research the usage of descriptive approach, with a population of 50 people. The number of samples is 50 students with a population sampling technique. Analysis of the data used, descriptive analysis, prerequisite test analysis, factor analysis and hypothesis testing. The results of the factor analysis showed that there were 3 factors that influenced the low learning outcomes, namely factor 1 (variables of motivation and learning methods), factor 2 (variables of physical health conditions, building conditions and parental upbringing). And factor 3 (interest variable, method and media). The results of the F test were 0.002 <0.05, and F count 5.570 > F table 2.81. So, together the independent variables (X1, X2, X3) have a effect on the dependent variable (Y). The t test on XI gets the result t count 3.969 > t table which is 2.012, a significance of 0.000 <0.05, So variable X1 has a significant effect on variable Y. The t test on X2 gets the result t count 2.129 > t table 2.012 significance 0.039 <0.05 , Then the X2 variable has a significant effect on the Y variable. The t test on X3 gets the result t count 1.566 < t table, namely 2.012 and a significance of 0.124 > 0.05, So the X3 variable has no effect on the Y variable. 26.6% low learning outcomes PAI-BP High grade at SD Negeri 166/III Cut Mutia is influenced by variables X1, X2, X3. And the remaining 73.4% is encouraged by using other variables.